Effect of Purpureocillium lilacinum on Root Lesion Nematode, Pratylenchus thornei - İlker Kepenekçi; Erçin Oksal; Refik Buzboğa; Halil Toktay; Mustafa İmren (Journal of Agricultural Sciences)
Wheat (Triticum spp.) is highly susceptible to the root lesion nematode, Pratylenchus thornei, which causes excessive amounts of crop losses each year. In this research, we investigated the cumulative effect of the biocontrol agent Purpureocillium lilacinum (syn: Paecilomyces lilacinus) against P. thornei. Three doses of P. lilacinum (106, 107 and 108 conidia cultures mL-1) with one dose of 400 P. thornei individuals (adults and juveniles) mL-1 were applied in 100 cm3 soil under greenhouse conditions. The number of nematodes in the soil and root in addition to total nematode in soil+root were determined. Moreover, different plant parameters such as the plant height, plant fresh and dry weight, root fresh and dry weight were evaluated. Applications with the higher dose of bio-agents (100 cm3 P. thornei infested soil with 108 conidia culture of P. lilacinum mL-1) exhibited maximal enhancement in dry and fresh weight of shoot and reduced P. thornei population. As a consequence, P. lilacinum individually was highly effective in enhancing different plant parameters and suppressing P. thornei reproduction. Overall, present findings suggest that the exploitation of the biocontrol agent P. lilacinum could be helpful for effective management of the root lesion nematode P. thornei.